Gut bacterial microbiota and obesity. (2nd March 2013) - Million, M.; Lagier, J.‐C.; Yahav, D.; Paul, M.
Abstract Although probiotics and antibiotics have been used for decades as growth promoters in animals, attention has only recently been drawn to the association between the gut microbiota composition, its manipulation, and obesity. Studies in mice have associated the phylum Firmicutes with obesity and the phylum Bacteroidetes with weight loss. Proposed mechanisms linking the microbiota to fat content and weight include differential effects of bacteria on the efficiency of energy extraction from the diet, and changes in host metabolism of absorbed calories. The independent effect of the microbiota on fat accumulation has been demonstrated in mice, where transplantation of microbiota from obese mice or mice fed western diets to lean or germ‐free mice produced fat accumulation among recipients. The microbiota can be manipulated by prebiotics, probiotics, and antibiotics. Probiotics affect the microbiota directly by modulating its bacterial content, and indirectly through bacteriocins produced by the probiotic bacteria. Interestingly, certain probiotics are associated with weight gain both in animals and in humans. The effects are dependent on the probiotic strain, the host, and specific host characteristics, such as age and baseline nutritional status. Attention has recently been drawn to the association between antibiotic use and weight gain in children and adults. We herein review the studies describing the associations between the microbiota composition, its manipulation, and obesity.